Promoting pro-environmental behaviour: existing evidence and policy implications - Lucas, K; Brooks, M; Darnton, A; Jones, J (Elsevier, 2008)
This paper describes a recent study in the UK aimed at identifying how policy makers might more effectively encourage pro-environmental behaviours amongst their target audiences. The study included analysis and synthesis of theories and models of behaviour change, a range of current policy programmes and instruments and 'real world' practices of individuals, households, groups and organisations. The paper highlights some important considerations for future policy within the UK and, more widely, for other countries aiming to introduce comprehensive and multi-level policy programmes to encourage pro-environmental behaviours. To this end, it emphasises the complex and non-linear nature of environmental behaviours and, thus, the importance of adopting multi-levelled and multi-instrument integrated policies across whole systems of delivery.